(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
Kindergarten education of gipsy children has been in focus for a long time in Hungary. Experts agree that successful participation in kindergarten education is an advantage in primary education. The gipsy ethnic minority has disadvantages in the labour market mainly due to their low-education (drop away from primary schools, low rate in vocational training, infinitesimally low number of students in grammar schools and tertiary education). It is gratifying that the number of gipsy children attending kindergarten has been quadrupled since 1970. The reality in nowadays Hungarian kindergartens is that children coming from bad circumstances, including gypsies, mean problems because the major of these institutes suit the socializing norms of low-middle class families. No wonder that even the teachers of these institutes are against gipsy kids.